Studenci z niepełnosprawnością w środowisku akademickim szkoły wyższej = Students with disabilities in the academic world - Adaszyńska, Ewa; Kuncewicz, Małgorzata (Vilnius: Mykolas Romeris Universitetas)
The students with disabilities have full rights of the effective and active functioning in the educational and social space of the university. The task of the academic community is to create favourable conditions for studying and learning and participating in the academic life, as well as to take measures to counteract the social and environmental inequality.
Keywords: studenci z niepełnosprawnością; równe traktowanie; Uniwersytet Zielonogórski; students with disabilities; equality; University of Zielona Góra